NEUROMARKETING IN INTERNATIONAL COMMERCIAL LAW - Carmen Tamara UNGUREANU; Aura Elena AMIRONESEI (Challenges of the Knowledge Society)
Commercial advertising is absolutely necessary for traders who promote their products and services in order to attract consumers and to succeed on the market at the expense of their competitors. As consumers have developed resistance to traditional marketing practices, traders may make use of neuromarketing techniques while searching for other efficient tools. Neuromarketing is a field that combines neurology, behavioral psychology and notions of economy and traditional marketing for the purpose of analyzing and understanding the processes that take place in the human brain when it is exposed to marketing stimuli. Neuromarketing raises certain ethical and legal issues. On the one hand, there are concerns related to the protection of the persons involved in neuromarketing research. On the other hand, applying in commercial advertising the solutions offered by neuromarketing poses a series of problems, since these solutions have been qualified as techniques that distort the rational consumer’s choice of products and services. Given that on the background of the technological revolution the consumer (of advertising) has become an international one, the paper will be structured in three parts. First, we will tackle the meaning of neuromarketing and how its techniques are used in commercial advertising, particularly in online advertising. In the second part, we will reveal the mechanism of online and offline neuromarketing, highlighting the legal issues stemmed from the neuromarketing research, especially from the participants data protection. In the last part, we will analyze the effects of neuromarketing on the single European market. Within this framework, we will establish the effects of neuromarketing on competition and consumers’ rights, determining the competent authority and the applicable law for dispute resolution.